Decision Making System While the Garbage Shelter Using Multiple Attribute Fuzzy Decision Making - Nungsiyati Nungsiyati; Novita Andriyani; Rizky Purnama (Institut Bakti Nusantara, 2022)
It is recognized that the choice of location Discharge the Waste Temporary are complicated considering the many factors to consider. It is therefore necessary criteria that can be used to determine the proper waste sites and meet the requirements. The requirement was confirmed in the Indonesian National Standard (SNI) 03-3241-1994 about election procedures landfill. This study is based on regional stages, where the stages to produce a map that shows the area within the planning area is divided into several zones eligibility. Simple Additive Weighting makes it easy to perform data analysis for decision making is very good, good and less good a selected location